Enhancing Mathematical Thinking Skills through Realistic Mathematics Education Assisted by an Ethnomathematics Mobile Module - Rahayu, Ratri; Fahma, Marizka Aulia; Bintoro, Henry Suryo; Murti, Alif Catur (FKIP Universitas Lampung, 2025)
This study addresses the deficiencies in students' mathematical thinking skills. A preliminary assessment of 69 students yielded a mean score of 21.32. The study examined enhancing students' mathematical thinking skills through the Realistic Mathematics Education (RME) model, supported by the ethnomathematics mobile module. This quantitative research employs a quasi-experimental design. The researchers collected data using a mathematical thinking skills test and analyzed it through an independent sample t-test and N-gain test. The findings indicate a significant improvement in the experimental group's posttest mean score, which increased to 80.72, surpassing the control group's posttest mean score of 69.49. The results confirm a significant difference in mathematical thinking skills between students taught using the RME approach with the ethnomathematics mobile module and those instructed through traditional lectures. The pretest-posttest data for the experimental group yielded an N-gain score of 0.59, classified as moderate. The study concludes that implementing the RME model with the ethnomathematics mobile module effectively enhances seventh-grade students' mathematical thinking skills in data presentation. The findings suggest that the ethnomathematics mobile module should be incorporated into other mathematical topics to support students' learning further. Keywords: ethnomathematics mobile module, mathematics thinking skills, RME.